Changes in adhesion molecules: β-catenin, E-cadherin and Galectin-3 in cells of testicular seminoma - Młynarczyk, Grzegorz; Domian, Natalia; Kasacka, Irena (Frontiers in Oncology, 2023)
Introduction: The most common testicular tumors are seminomas. They are characterized by rapid growth and a very high potential for metastasis to other organs. Mutual interactions of tumor cells play an important role in the invasiveness and metastatic capacity, in which complexes of adhesion proteins play a special role. There is a lack of studies on changes in these molecules and their behaviour in testicular cancer. The aim of the study was immunohistochemical identification and evalutaion of adhesive molecules β-catenin, E-cadherin, galectin-3 in testicular cancer – seminoma. Methods: Tests were performed on sections of testicular cancer – seminoma in comparison with unchanged tissue samples as a control. Material was taken from 30 patients who underwent orchiectomy. Immunohistochemistry and PCR were used to identify β-catenin, E-cadherin and galectin-3 and gene expression. Results: Immunoreactivity and expression of β-catenin and E-cadherin in seminomas were markedly decreased compared to non-cancerous testicular tissue. Galectin-3 immunoreactivity was found in both control and cancerous tissue, but in different location. In non-cancerous tissue, it was localized in the cytoplasm of the cells of the seminiferous tubules, in seminomas it was localized mainly in the endothelium. The expression of the Lgals3 gene encoding galectin-3 in seminomas was slightl higher in relation to the tissue unchanged by the carcinogenetic process. Conclusions: The results of the study suggest a significant role of β-catenin, E-cadherin and galectin-3 in the carcinogenesis of seminomas and may indicate new aspects of the patomechanism of seminomas formation, and thus time lead to a better understand the biology of these tumors.